Animals in Saxon & Scandinavian England : backbones of economy and society - Holmes, Matilda (Sidestone Press, 2014)
In this book an analysis of over 300 animal bone assemblages from English Saxon and Scandinavian sites is presented. The data set is summarised in extensive tables for use as comparanda for future archaeozoological studies. Animals in Saxon and Scandinavian England takes as its core four broad areas of analysis. The first is an investigation of the diet of the population, and how food was used to establish social boundaries. Increasingly diverse diets are recognised, with high-status populations distinguishing themselves from other social sectors through the way food was redistributed and the d.